2016
DOI: 10.4103/0970-9290.179840
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral maxillary fourth and fifth molars: An unusual radiographic appearance

Abstract: Distomolars are supernumerary teeth present distal to third molars. Although many cases of bilateral fourth molars are reported, very few cases having bilateral fifth molars are described in literature. Here, we present a case having bilateral impacted maxillary fourth and fifth molars with the fifth molar on the left side having an unusually small appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…19 Respecto al sexo, la mayoría de los reportes casos, así como los estudios de prevalencia de supernumerarios indican que los dientes paramolares se presentan más en hombres que en mujeres, dicha situación no se dio en este caso. 14,19,21,23 Investigaciones realizadas por Santos et al 12 y Martinez-Gonzalez et al 19 mencionan que los dientes supernumerarios retenidos pueden asociarse a quistes o agrandamiento del folículo de hasta 3 mm, en el caso presentado, en ninguno de los paramolares se observó dicha condición.…”
Section: Discussionunclassified
“…19 Respecto al sexo, la mayoría de los reportes casos, así como los estudios de prevalencia de supernumerarios indican que los dientes paramolares se presentan más en hombres que en mujeres, dicha situación no se dio en este caso. 14,19,21,23 Investigaciones realizadas por Santos et al 12 y Martinez-Gonzalez et al 19 mencionan que los dientes supernumerarios retenidos pueden asociarse a quistes o agrandamiento del folículo de hasta 3 mm, en el caso presentado, en ninguno de los paramolares se observó dicha condición.…”
Section: Discussionunclassified
“…Paramolars are rudimentary ST that might develop buccally or lingually to the molar series. [1][2][3][4][5] Distomolars are either eumorphic or dysmorphic in shape. 6,7 ST can be presented as horizontal, vertical, or inverted orientation and can be classified as fully or partially erupted and impacted.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ST management should be part of a comprehensive treatment plan. 1,13 The review of literature revealed that distomolars are more prevalent in females than in males, 3,4,8,10,[13][14][15][16][17][18] while others indicated that distomolars are dominant in males. 2,9,11,19,20 Most researchers mentioned that distomolars are present in the maxilla, 4,[6][7][8][9][10]14,16 whereas others stated that distomolars are frequently found in the mandibular arch.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations